Analytical and Computational Fluid Dynamics Methods for Determining the Torque and Power of a Vertical-Axis Wind Turbine with a Carousel Rotor - Filip Lisowski; Marcin Augustyn (Applied Sciences)
This paper presents the results of experimental, analytical, and numerical studies on determining the driving torque and power of a vertical-axis wind turbine (VAWT) with planetary blade motion forced by a carousel rotor. First, experimental studies in the wind tunnel laboratory were conducted to determine the tip speed ratio λ for the real-scale wind turbine model under self-starting conditions. Then, an analytical kinematic model of the turbine was developed. Finally, computational fluid dynamics (CFD) analysis was conducted to verify the analytical approach and examine aerodynamic interferences between particular turbine blades. The main objective of the study was to verify the accuracy of the simplified analytical approach to calculating the driving torque and turbine power compared to the numerical results based on 2D analysis using computational fluid dynamics. The obtained results showed good agreement considering the modeling of the motion of the three dual-coherent blades of the wind turbine. Comparing the analytical and CFD approaches, the error in determining the average driving torque and the average turbine power was about 1%. An additional objective of the study was to use the developed analytical method to calculate the starting torque and demonstrate the main advantage of the carousel wind rotor, which is its higher starting torque compared to the H-type Darrieus rotor.